IMPLEMENTATION OF LOCAL INGREDIENT-BASED SUPPLEMENTARY FEEDING FOR STUNTING TODDLERS WITH ANIMATION MEDIA ON PAITON VILLAGE - Iis Hanifah; Tutik Hidayati (Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2024)
The prevalence of stunting in Indonesia based on Riskesdas in 2018 decreased by around 7.2% from 37.2% of the national stunting prevalence in 2017, but this figure is still below the target set by WHO, which is below 20%. The prevalence of stunting in East Java, contributes as much as 20%. The prevalence of stunting in Java is 26.7%. The stunting rate in Probolinggo Regency is quite high. Probolinggo Regency is one of the stunting priority districts in East Java with a stunting percentage of 42.5%, which means that the stunting problem in Probolinggo Regency is a serious problem. The purpose of this study is to analyze the effect of implementing local-based supplementary feeding for stunting toddlers with animation media on Paiton Village. The design used in this study used Pre-Experimental Design One Group Pre-Post-Test design. The number of samples was 40 mothers under five, Data collection techniques in this study by identifying respondents in accordance with research criteria. The primary data was obtained directly by involving the village midwife responsible for Paiton Village. This study used questionnaires as a data collection tool. The analysis used in this study was the Wilcoxon Sign Rank Test. The results of the study found that there was an influence on the application of local-based supplementary feeding for stunting toddlers with animation media on Paiton Village